EFFECT OF SALINITY ON CALLUS FORMATION AND ORGANOGENESIS OF RED KIDNEY BEANS (PHASEOLUS VULGARIS L.) - Thiagarajan, Thippi; Recinos, Helly; Tillett, Arlitta (European Scientific Journal, ESJ, 2013)
The global warming and its effect on sea level raise is an undisputed fact that has been supported by numerous studies. Countries such as Belize with large area of land just above sea level will face problems due to increased soil salinity. The sea level raise will also affect our fresh water supplies due to back flow in to our rivers. These all will have effect on agriculture since many crops cannot tolerate the increased salinity level. Development of resistant varieties of crops that can withstand moderate level of salinity can help to mitigate the problems of food shortage in the future. Tissue culture or micropropagation can be an effective technique for the in vitro development of salt resistant varieties of crops. Initially an experiment was carried out to test the effect of hormones on callus formation of red kidney beans (Phaseolus vulgaris L.). Callus tissue was initiated on MS medium supplemented with various hormones (IAA, IBA and 2,4 D) by using explants from epicotyle. Based on the fresh weight produced during the incubation period, 2,4-D was identified as the best hormone for callus growth. After choosing the best hormone for callus generation under in vitro conditions, the effect of salinity on callus regeneration and organogenesis of P. vulgaris was tested under in vitro conditions. Although callus regeneration occurred in all of the salt concentration used in the experiment, the callus regeneration decreased as the concentration of the salt increased. Microscopic evidence of organogenesis was observed as the callus tissue has differentiated in to roots, root hairs and vascular tissues under in vitro saline conditions.